Measurement uncertainty in the analysis of selected polycyclic aromatic hydrocarbons in environmental water by magnetic molecularly imprinted polymer-based micro-solid phase extraction- liquid chromatography - Kamaruzaman, Sazlinda; Loh, Saw Hong; Che Abdullah, Nor Syuhadaa; Ariffin, Marinah Mohd; Wan Mohd Khalik, Wan Mohd Afiq; Yusoff, Farhanini (Malaysian Analytical Sciences Society, 2024)
Sample preparation is important to produce a clean extract to enhance detection sensitivity and minimize instrument maintenance. A micro-solid phase extraction (µ-SPE) technique using magnetic molecularly imprinted polymers (magnetic-MIPs) as the adsorbents combined with micro-high performance liquid chromatography and ultraviolet detection (µ-HPLC-UV) has been developed for the determination of selected polycyclic aromatic hydrocarbons (PAHs), namely benzo[a]pyrene, phenanthrene, fluoranthene and pyrene in environmental water samples. The magnetic-MIPs were characterized using scanning electron microscopy, Brunauer–Emmett–Teller, thermogravimetric analysis and vibrating sample magnetometer to finalize the physical properties of the magnetic-MIPs. The µ-SPE was then optimized using one variable at a time approach to enhance the extraction efficiency. Under the optimal extraction conditions, the feasibility of using magnetic-MIPs as the adsorbents for the extraction of the selected PAHs was proven with a wide linearity range (5-250 µg L-1), good repeatability (relative standard deviation <10%), ultra-trace detection limits (0.01-0.02 µg L-1) and good relative recovery (80.2-119.3%) for the application in the environmental water. The doubt of using the µ-SPE was investigated by calculating the measurement uncertainty. The estimated combined standard uncertainties for the determination of the selected PAHs were in the range of 0.0678-0.0890. It was concluded that the uncertainty of the µ-SPE-µ-HPLC-UV is mainly attributed to its accuracy. Nevertheless, the results showed that the measurement uncertainty of the proposed magnetic-MIPs-based µ-SPE-µ-HPLC-UV was at an acceptable level. The method is beneficial to the routine analysis, especially in providing simple and sensitive determination of the selected PAHs in environmental water. The µSPE technique consumes minimal amounts of solvent and traces of adsorbents, which then greatly minimizes the waste and analysis costs in routine analysis.